THE ROLE OF EDUCATION IN EFFORTS TO PREVENT THE CRIMINAL ACT OF HUMAN TRAFFICKING IN INDONESIA - Devi Rahayu; Dyah Nan Sulisetyaningsih; Unun Kholisa Rosyitawati; Dippo Alam (STMIK Indonesia Banda Aceh, 2026)
Human trafficking is a form of crime that threatens human rights and negatively impacts social life . Prevention efforts are not only carried out through law enforcement , but also require the role of education in building legal awareness , humanitarian values , and the community's ability to recognize various forms of human trafficking . This study aims to analyze the role of education in preventing the crime of human trafficking in Indonesia and identify challenges in implementing prevention education in schools and communities . This study uses a library research method with a qualitative descriptive approach . Data were obtained from laws and regulations , books , scientific articles , and other relevant documents . The results of the study indicate that education has a strategic role in increasing legal literacy , shaping students ' character , and instilling awareness of the dangers of human trafficking from an early age . Integration of material on human rights , child protection , and the dangers of human trafficking in the learning process can increase students' awareness of various crime modes . However, the implementation of prevention education still faces various obstacles , such as limited teaching materials , a lack of educator competence , and minimal collaboration between educational institutions , the government , and the community . Therefore , curriculum strengthening , educator capacity building , and cross- sector collaboration are needed so that education can function optimally as a preventive strategy in preventing human trafficking in Indonesia.